⁠Marine Biodiversity Conservation: A Bibliometric Study on Ocean Research and Policy - Judijanto, Loso (Westscience Press, 2025)
Marine biodiversity is essential for sustaining ocean health, ecological balance, and human livelihoods, yet it faces escalating threats from climate change, overexploitation, and habitat degradation. This study conducts a comprehensive bibliometric analysis to map the evolution and thematic structure of scholarly research on marine biodiversity conservation from 2000 to 2024. Using Scopus-indexed data and VOSviewer software, the study analyzes keyword co-occurrence, collaboration networks, and temporal trends in the literature. Results indicate that “biodiversity,” “marine environment,” and “conservation” are central research themes, while emerging topics such as “physiology,” “nonhuman,” and “controlled study” reflect recent shifts toward micro-level and experimental research. The study also reveals the increasing integration of policy-oriented topics, such as marine protected areas and environmental governance, with core ecological concepts. Despite this progress, the analysis highlights geographical imbalances and underexplored areas, including traditional knowledge systems and economic valuation of marine ecosystems. This bibliometric mapping provides valuable insights for guiding future research agendas, enhancing global collaboration, and strengthening the science-policy interface in marine biodiversity conservation.